Psychosocial and functional outcomes in young adults with childhood‐onset epilepsy: a 10‐year follow‐up. (27th January 2020) - Friefeld Kesselmayer, Rachel; McMillan, Taylor; Lee, Beatrice; Almane, Dace; Hermann, Bruce P; Jones, Jana E
Abstract : Aim: To compare long‐term psychosocial and functional outcomes of young adults with uncomplicated childhood‐onset epilepsy (COE) to population norm controls utilizing a controlled prospective cohort study. Method: Psychosocial and functional outcomes were assessed at 10‐year follow‐up. Fifty‐three young adults (27 males, 26 females) with COE ( n =21 remission; 18y 1mo–30y 9mo; mean age 23y 4mo [SD 3y 4mo]; mean age of epilepsy onset 12y [SD 3y 2mo]) were compared to 55 (23 males, 32 females) first‐degree cousin controls (18y 5mo–29y 8mo; mean age 23y 6mo [SD 3y]). Seizure remission status and baseline comorbidities (attention‐deficit/hyperactivity disorder [ADHD], depressive disorders, anxiety disorders, and academic problems) were examined as possible risk factors for significant differences in functional outcomes. Results: Poorer functional outcomes, indicated by patient rated cognition and overall disability, were evident among young adults with epilepsy compared to controls (all p <0.05). These difficulties were due to baseline comorbid ADHD and academic problems. Remission status was not related to measured cognition and overall disability. Interpretation: Psychosocial outcomes of young adults with COE were similar to controls. In contrast, functional outcomes were worse in epilepsy across cognition and overall disability. Baseline comorbid ADHD and academic problems were identified as risk factors at 10‐year follow‐up suggesting that these early recognized comorbidities at or near diagnosis have long‐term impacts. What this paper adds: Young adults with childhood‐onset epilepsy (COE) and controls have similar psychosocial outcomes 10 years after diagnosis. Young adults with COE report greater limitations in cognition and overall disability than controls. Baseline presence of attention‐deficit/hyperactivity disorder and academic problems significantly affect cognitive and overall disability scores. What this paper adds: Young adults with childhood‐onset epilepsy (COE) and controls have similar psychosocial outcomes 10 years after diagnosis. Young adults with COE report greater limitations in cognition and overall disability than controls. Baseline presence of attention‐deficit/hyperactivity disorder and academic problems significantly affect cognitive and overall disability scores. This article is commented on by Speechley on pages 542–543 of this issue.